PROMOTIONAL PLAN FOR RELEASE OF APRI STUDY (Tufts Archival Research Center, 2007)
Marginalia; Memorandum from Dennis Birch and Eric Shulman to Cal George discussing promotional plan for release of A. Philip Randolph Institute (APRI) study. States that the APRI study shows that low- and middle-income African-Americans are harder hit by excise taxes than are higher income Americans. Argues this is proof that excise taxes are regressive and unfair. Proposes a press conference, op-ed program, satellite interviews, and study distribution.